2019
DOI: 10.1039/c9ob00145j
|View full text |Cite
|
Sign up to set email alerts
|

Development of ergosterol peroxide probes for cellular localisation studies

Abstract: Cell-permeable ergosterol peroxide probes were synthesized to advance their biological understanding and therapeutic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…A more rigorous report guided by the principle that a set of negative controls was required to conduct washout experiments of the EP probe, and orthogonal fluorescent chromophores had to be synthesized for live cell studies. 69 Also, the cell lines with fluorescently-tagged organelle were generated to compliment the use of organelle trackers. The hydroxyl group at C-3 of the EP was the direct coupling site for the biotin and chromophores to avoid any further chemical modification of the EP that could interfere with its naive action (compounds 11d – g , Figure 10 ).…”
Section: Triterpenoid Chemical Probesmentioning
confidence: 99%
“…A more rigorous report guided by the principle that a set of negative controls was required to conduct washout experiments of the EP probe, and orthogonal fluorescent chromophores had to be synthesized for live cell studies. 69 Also, the cell lines with fluorescently-tagged organelle were generated to compliment the use of organelle trackers. The hydroxyl group at C-3 of the EP was the direct coupling site for the biotin and chromophores to avoid any further chemical modification of the EP that could interfere with its naive action (compounds 11d – g , Figure 10 ).…”
Section: Triterpenoid Chemical Probesmentioning
confidence: 99%
“…Moreover, fourteen known compounds, including eight triterpenoids, hexagonin F ( 3 ) [ 30 ], sinensoic acid ( 4 ) [ 31 ], 24( E )-3 β -hydroxylanosta-8,24-dien-26-al-21-oic acid ( 5 ) [ 32 ], trametenolic acid ( 6 ) [ 33 ], eburicoic acid ( 7 ) [ 34 ], 24-methylenelanost-8-en-3-ol ( 8 ) [ 35 ], eburicodiol ( 9 ) [ 36 ], and gloeophyllin B ( 10 ) [ 37 ]; four steroids, ergosterol peroxide ( 11 ) [ 38 ], ergosterol ( 12 ) [ 39 ], (22 E )-ergosta-7,22-dien-3 β -ol ( 13 ) [ 40 ], and (22 E ,24 R )-5-hydroxy-5 α -ergosta-7,22-diene-3,6-dione ( 14 ) [ 41 ]; and two isocoumarins, oospoglycol ( 15 ) [ 42 ] and oospolactone ( 16 ) [ 43 ], were identified. In addition, eleven known constituents, including one triterpenoid, lupeol ( 17 ) [ 44 ]; seven steroids, ergosterol peroxide ( 11 ), (22 E )-ergosta-7,22-dien-3 β -ol ( 13 ), (22 E ,24 R )-5-hydroxy-5 α -ergosta-7,22-diene-3,6-dione ( 14 ), 9,11-dehydroergosterol peroxide ( 18 ) [ 45 ], 5,8-epidioxy-(5 α ,8 α ,22 E )-ergosta-6,22-dien-3-one ( 19 ) [ 46 ], ergosta-7,22-diene-3-one ( 20 ) [ 40 ], and stigmast-4-en-3-one ( 21 ) [ 47 ]; and three benzenoids, syringic acid ( 22 ) [ 48 ], isovanillic acid ( 23 ) [ 49 ], and tyrosol ( 24 ) [ 50 ], were characterized from the fruiting bodies of T. suaveolens . The known compounds were identified by comparison of their physical and spectroscopic data with those previously published.…”
Section: Resultsmentioning
confidence: 99%
“…Compound 14 was reported to attenuate the growth and triggered an apoptotic process in prostate cancer cells [ 55 ]. Inhibition of various tumor cell lines by compound 19 was also determined [ 46 ]. Based on our anti-inflammatory examination results and reported bioactivities in the literature, it can be concluded that the fruiting bodies of T. cubensis and T. suaveolens could be promising as anti-inflammatory lead drugs or natural, healthy ingredients.…”
Section: Resultsmentioning
confidence: 99%
“…A series of EP analogs containing BODIPY or a biotin moiety was obtained by Rivas et al as probes for cellular localization studies [ 149 ]. They demonstrated that EP is distributed across the cytosol with significant accumulation in the endoplasmic reticulum.…”
Section: Endoperoxidesmentioning
confidence: 99%